By-Laws - Jamaica Association of Montreal (JAM) (2021)

Jamaica Association of Montreal Newsletter : Oct. - Dec. 2021 : Vol. 22 - Jamaica Association of Montreal (JAM) (2021)

December 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)

Reisaction Newsletter : no. 30 - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

November 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)

Gun Violence in Montréal : Context, Causes, Reactions, and Recommendations - Pettem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2021)
Montréal has recently been experiencing an unprecedented spike in gun violence, primarily perpetrated by a younger demographic. These shootings are occurring more frequently in broad daylight, in the midst of populated urban areas (Magder). As of August 31, the Montréal police (the SPVM) had documented 77 separate firearms being discharged, with 360 bullets being fired in roughly 100 shootings. This has already surpassed total instances for 2019 and 2020. 654 firearms have been seized, furthermore, the highest ever for the SPVM. This has led to 23 homicides, which is already rapidly approaching the 25 that were observed in both 2019 and 2020 (Perron).

Semaji - Black Community Resource Centre (BCRC) (2021)

October 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)

Jamaica Association of Montreal Newsletter : Jul. - Sept. 2021: Volume 21 : Summer 2021 Edition - Jamaica Association of Montreal (JAM) (2021)

September 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Directory of Services - Jamaica Association of Montreal (JAM) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Jamaica Association of Montreal Newsletter : Apr. - June. 2021 : Vol. 20 - Jamaica Association of Montreal (JAM) (2021)

June 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)

May 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

April 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)

Jamaica Association of Montreal Newsletter : Jan. - Mar. 2021 : Vol. 19 - Jamaica Association of Montreal (JAM) (2021)

March 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)

Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Survey of MCLL Moderator Engagement : Report to the MCLL Council - McGill Community For Lifelong Learning (MCLL) (2021)
In December 2019, Council requested that the Planning Committee create and administer a survey of moderators to inquire about their engagement in the MCLL community in the service of retaining and recruiting moderators. Due to the COVID-19 outbreak and the high-priority burden the pandemic put on various committees, the survey was delayed until late in the Fall 2020 term. This document reports on the survey results and includes, in appendices, the survey questions as well as the detailed results including all comments received by respondents.

Semaji - Black Community Resource Centre (BCRC) (2021)

Harnessing your Transferable Skills in a COVID-19 Economy - Khamala, Maya (2021)

Job Search Mentorship During COVID-19 - Khamala, Maya (2021)

Skill-Building & Networking in the Time of COVID-19 - Khamala, Maya (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Activity Report 2020-2021 - Jamaica Association of Montreal (JAM) (2021)
The Association was founded in November 1962, shortly after Jamaica’s Independence in August 1962. Our seal of Incorporation was granted in 1970. Since its inception, the Association has grown strong in attracting members. It is recognized as the official organization representing Jamaicans in Montreal at the Federal, Provincial and Municipal levels. We have accompanied delegations and presented briefs to all levels of government. Given our commitment to community development, the Jamaica Association developed our Mission Statement as follows: “To assist in improving and enhancing the quality of life for the Jamaican Community”.

Annual Report : 2020-2021 - McGill Community For Lifelong Learning (MCLL) (2021)

McGill Community For Lifelong Learning : Fall 2021 - McGill Community For Lifelong Learning (MCLL) (2021)

Moderators' Handbook - McGill Community For Lifelong Learning (MCLL) (2021)

The Newsletter - McGill Community For Lifelong Learning (MCLL) (2021)

The Newsletter - McGill Community For Lifelong Learning (MCLL) (2021)

The Newsletter - McGill Community For Lifelong Learning (MCLL) (2021)

Annual Report : Our Collective Impact 2020-2021 - NDG Community Council (NDGCC) (2021)

Rapport annuel : Notre impact collectif 2020-2021 - NDG Community Council (NDGCC) (2021)

2020-2021 Annual Report - The English Speaking Catholic Council (ESCC) (2021)

The Yellow Door : 2020-2021 Annual Report / La Porte Jaune : 2020-2021 Rapport annuel - Yellow Door (2021)

The Yellow Door : Frequently Asked Questions - Yellow Door (2021)

The Yellow Door Press Kit - Yellow Door (2021)

Fall Program Book : September - December 2021 - Youth Employment Services (YES) (2021)

Showing up When it Counts : 2021 Annual Report - Youth Employment Services (YES) (2021)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)